Pengaruh Perendaman dengan Perbedaan Level Kitosan terhadap Indek Putih, Haugh Unit, dan pH Putih Telur Itik - Eli Sahara; Sofia Sandi; Fitra Yosi; Avin Bastian (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Sahara E, Sandi S, Yosi F, Bastian A. 2019. The effect of use chitosan solution in the immersion proces on egg quality. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 287-291. Palembang: Unsri Press. Eggs are a commodity of poultry that can be easily damaged if stored at room temperature for a long time. Chitosan has anti-microorganism properties and can be used to extend the shelf life of eggs. The purpose of this study is to extend the shelf life of eggs by soaking chitosan solution and maintaining egg quality. The study used a completely randomized design (CRD) of 6 treatments, 4 replications and each replication consisted of 2 eggs. The treatment is; P0=0% chitosan, P1=0.5% chitosan, P2=1% chitosan, P3=1.5% chitosan, P4=2% chitosan and P5=2.5% chitosan. Eggs are stored for 14 days at room temperature after being soaked in chitosan solution for 24 hours. The parameters measured are; egg white index,, haugt unit and egg white pH. The results showed that immersion of eggs in chitosan solution 0.5% (P1) gave an egg white index of 0.075 significantly better than the control of 0.05, the highest real haugh unit value of all treatments was 84. The pH of the egg white soaked with Chitosan solution is the same, but lower than the control. The conclusion of this study is the treatment of P1 (0.5% chitosan) shows the best haugh unit value which is 10.71% higher than the control.Keywords: chitosan, ducks, eggs, quality, solution